2013
DOI: 10.1093/jrr/rrt065
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acute hypoxia and radiation quality on cell survival

Abstract: To measure the effect of acute oxygen depletion on cell survival for different types of radiation, experiments have been performed using Chinese hamster ovary (CHO) cells and RAT-1 rat prostate cancer cells. A special chamber has been developed to perform irradiations under different levels of oxygenation. The oxygen concentrations used were normoxia (air), hypoxia (94.5% N2, 5% CO2, 0.5% O2) and anoxia (95% N2, 5% CO2). Cells were exposed to X-rays and to C-, N- or O-ions with linear energy transfer (LET) val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 34 publications
(40 reference statements)
4
68
0
Order By: Relevance
“…20 In clonogenic experiments, this effect can be expressed as the OER, that is, the ratio of dose required to kill a given fraction of cells in hypoxic vs oxic conditions. Various investigators have demonstrated that OER decreases with increasing LET, with Barensden 9 finding that OER reached 1 with LET of 165 keV mm 21 . 21 Thus, cells within relatively hypoxic and therefore radioresistant areas of tumour are likely to be more effectively killed by radiation of LET .100 keV mm 21 .…”
Section: Oxygen Enhancement Ratiomentioning
confidence: 99%
See 3 more Smart Citations
“…20 In clonogenic experiments, this effect can be expressed as the OER, that is, the ratio of dose required to kill a given fraction of cells in hypoxic vs oxic conditions. Various investigators have demonstrated that OER decreases with increasing LET, with Barensden 9 finding that OER reached 1 with LET of 165 keV mm 21 . 21 Thus, cells within relatively hypoxic and therefore radioresistant areas of tumour are likely to be more effectively killed by radiation of LET .100 keV mm 21 .…”
Section: Oxygen Enhancement Ratiomentioning
confidence: 99%
“…Various investigators have demonstrated that OER decreases with increasing LET, with Barensden 9 finding that OER reached 1 with LET of 165 keV mm 21 . 21 Thus, cells within relatively hypoxic and therefore radioresistant areas of tumour are likely to be more effectively killed by radiation of LET .100 keV mm 21 .…”
Section: Oxygen Enhancement Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…Alpha particles are considered more cytotoxic than beta particles, especially under hypoxic conditions (23,24) and, because of their higher biological efficacy, the required activity is lower than that of beta particles.…”
Section: Abstract 223 Ra Prolongs Overall Survival In Symptomatic Pamentioning
confidence: 99%